One-Month Outcomes of Intravitreal Anti-VEGF vs. Dexamethasone Implant in the Treatment of Diabetic Macular Edema in Vitrectomized Eyes - Liang, Youling; Yan, Bin; Xie, Manyun; Meng, Zhishang; Ma, Jiayue; Ma, Bosheng; Luo, Jing (Frontiers in Medicine, 2022)
Objectives: To compare short-term effect of intravitreal ranibizumab with dexamethasone implant for diabetic macular edema (DME) in vitrectomized eyes. Methods: Single-center, randomized, subject-masked study of vitrectomized eyes with DME. Study eyes were divided into two groups, receiving ranibizumab (IVA group, n=35 eyes) or dexamethasone implant (IVD group, n=35 eyes) respectively. Results: Baseline best-corrected visual acuity (BCVA) and central retinal thickness (CRT) were similar in the two groups. At Week 1, the CRT improvement was significant in two groups (P=0.041 in IVA group, P=0.030), but at Month 1, only IVD group had significant improvement in CRT (P<0.001). And BCVA gains were significant at Week 1 (P=0.029) and Month 1 (P=0.001) in IVD group, whereas IVA group did not show significant BCVA gains (P=0.056 at Week1, P=0.166 at Month 1). The changes of BCVA and CRT were significantly higher in IVD group than IVA group at Month1, but the changes were not significant at Week1. Conclusions: Dexamethasone implant is effective in vitrecomized eyes with DME, improving of BCVA and reduction of CRT were significantly greater compared with the anti-VEGF therapy.